The grounding of temporal metaphors. (March 2016) - Lai, Vicky T.; Desai, Rutvik H.
Abstract: Grounded cognition suggests that the processing of conceptual knowledge cued by language relies on the sensory-motor regions. Does temporal language similarly engage brain areas involved in time perception? Participants read sentences that describe the temporal extent of events with motion verbs ( The hours crawled until the release of the news ) and their static controls. Comparison conditions were fictive motion ( The trail crawled until the end of the hills ) and literal motion ( The caterpillar crawled towards the top of the tree ), along with their static controls. Several time sensitive locations, identified using a meta-analysis, showed activation specific to temporal metaphors, including in the left insula, right claustrum, and bilateral posterior superior temporal sulci. Fictive and literal motion contrasts did not show this difference. Fictive motion contrast showed activation in a conceptual motion sensitive area of the left posterior inferior temporal sulcus (ITS). These data suggest that language of time is at least partially grounded in experiential time. In addition, motion semantics has different consequences for events and objects: temporal events become animate, while static entities become motional.